Communicating Photograph Content Through Tactile Images to People With Visual Impairments - Pakėnaitė, Karolina; Nedelev, Petar; Kamperou, Eirini; Proulx, Michael J.; Hall, Peter M. (Frontiers in Computer Science, 2022)
Millions of people across the world are currently denied access to visual images. People with visual impairment are denied the simple pleasures of viewing family photographs, enjoying the pictorial embellishment of news stories, and are unable to benefit from photographs in textbooks, tourist brochures, and so on. We propose a simple, inexpensive but effective approach, to make content accessible via touch. We use state-of-the-art algorithms, to automatically process an input photograph into a collage of icons that depict the most important semantic aspects of a scene. This collage is printed onto swell paper. Our experiments show that people can recognise content to an accuracy exceeding 70% and create plausible narratives to explain the content. This means that people are able to understand image content via touch. Communicating scene foreground is a step forward, but there are many other steps needed to provide the visually impaired with the fullest possible access to visual content.